General phase-covariant quantum cloning - Lan-Lan Li; Wen-Hai Zhang; Ke Zhang; Cheng-Yu Fan (AIP Advances)
Phase-covariant quantum cloning has important applications in quantum cryptography. This paper proposes the unitary transformation of the optimal 1 → 2 general phase covariant quantum cloning in two dimensions and obtains the maximal fidelity of copies. In addition, an experimental scheme is designed to implement this unitary transformation using linear optical elements, and the scheme is feasible under the present experimental technology.